Care Arrangements of Older Adults: What They Prefer, What They Have, and Implications for Quality of Life. (23rd November 2018) - Kasper, Judith D; Wolff, Jennifer L; Skehan, Maureen
Abstract: Background and Objectives: Meeting individual preferences for long-term services and supports (LTSS) is a policy priority that has implications for quality of care. Evidence regarding preferences is sparse. In addition, little is known regarding whether preferences and care arrangements match for those receiving care, and implications for quality of life. Research Design and Methods: A random sample ( n = 1, 783 in 2012) of National Health and Aging Trends Study participants were asked the best care option for someone 80+ who needs help with personal care and mobility. Analyses examine variations in care preferences, the relationship of preferences to care arrangements, and the association of matched preference and care arrangements to quality of life indicators. Results: Care preferences vary by demographics. Equal proportions (3 in 10) of older adults chose assisted living or continuing care retirement communities (CCRC), care in own home with family help, and care in own home with paid help, as the best options. Persons in assisted living/CCRC settings were significantly more likely to choose this option as best. Only 1 in 3 older persons receiving care are in arrangements that match preferences. No association with quality of life indicators was found. Discussion and Implications: Aging in place remains the care preference of a majority, but close to one-third chose assisted living/CCRC, suggesting preferences are evolving. Aligning care preferences and arrangements is a policy goal, but many do not achieve a match and there remain gaps in understanding trajectories in preferences and care arrangements and implications for quality of life.